Post-conflict reconstruction: role of undp in sri lanka - Thangavel, K.B. (University of Jaffna, 2012)
The United Nations policy of opposing amnesties for war crimes, crimes against humanity, genocide or gross violations of human rights, including in the context of peace negotiations, represents an important evolution, grounded in long experience. Capacity development is fundamental to the broader objective of transforming fragile states into stable nations. A growing body of research on these issues is emerging, pointing to the lessons that have been learned in recent years. UNDP supports capacity development initiatives of national governments, civil society organizations, independent national and regional institutions and other stakeholders through advocacy, policy advisory and implementation services. With this background this paper tries to analyses the UNDP role in post–conflict reconstruction in Sri Lanka after the Eelam war IV and also analysing findings and formulating capacity development responses in Sri Lanka.